2010
DOI: 10.1177/0333102410368439
|View full text |Cite
|
Sign up to set email alerts
|

Nummular headache associated with focal hair heterochromia in a child

Abstract: Nummular headache (NH) is a recently described headache syndrome where continuous or intermittent pain is localised to a coin-shaped region of the skull. NH can be a primary headache disorder or secondary to intracranial or extracranial pathology. We report a four-year-old boy who presented with nummular headache co-localised with a patch of discoloured hair and propose a common aetiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 11 publications
1
13
0
1
Order By: Relevance
“…Patients, when explaining their symptoms, usually finger point to a specific area of the head. Some patients have shown trophic changes within the painful area, including thinness of the skin, and one patient had hair heterochromia at the pain site . There are a few cases reported with the painful area larger than 6 cm of diameter – up to 10 cm .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients, when explaining their symptoms, usually finger point to a specific area of the head. Some patients have shown trophic changes within the painful area, including thinness of the skin, and one patient had hair heterochromia at the pain site . There are a few cases reported with the painful area larger than 6 cm of diameter – up to 10 cm .…”
Section: Resultsmentioning
confidence: 99%
“…Some patients have shown trophic changes within the painful area, including thinness of the skin, 67 and one patient had hair heterochromia at the pain site. 68 There are a few cases reported with the painful area larger than 6 cm of diameter -up to 10 cm. 69,70 Some studies have shown evidence of increased sensitivity -a lower pain threshold with pressure algometry -restricted to the symptomatic area, with no pericranial tenderness in the remainder of the scalp, and with no signs of a generalized pain state.…”
mentioning
confidence: 99%
“…NH can be a primary headache disorder or secondary to intracranial or extra cranial pathology. There is a case report in the literature of a four-year-old boy who presented with nummular headache co-localized with a patch of discolored hair and a common etiology is proposed [ 75 ].…”
Section: Other Primary Headache Disordersmentioning
confidence: 99%
“…8 A solitary case of nummular headache associated with focal hair heterochromia in a child has also been reported. 9 Three different types of hair heterochromia have been previously described: patchy, segmental and diffuse. 10 The patient in the current case had heterochromia of one area of scalp hair and thus was diagnosed with patchy or focal heterochromia.…”
Section: Pramod Kumarmentioning
confidence: 99%